2012
DOI: 10.2174/156802612804910250
|View full text |Cite
|
Sign up to set email alerts
|

Equinatoxin II Potentiates Temozolomide- and Etoposide-Induced Glioblastoma Cell Death

Abstract: Glioblastoma (GBM) is considered incurable due to its resistance to current cancer treatments. So far, all clinically available alternatives for treating GBM are limited, evoking the development of novel treatment strategies that can more effectively manage these tumors. Extensive effort is being dedicated to characterize the molecular basis of GBM resistance to chemotherapy and to explore novel therapeutic procedures that may improve overall survival. Cytolysins are toxins that form pores in target cell membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…7 GBM cells are radio- and chemo-resistant; therefore, ways to increase cell death are one of the major targets in GBM research. 8, 9, 10 Moreover, the parenchymal infiltration of GBM cells makes total surgical resection an impossible task, 11 rendering the study of tumor invasion mechanisms an issue regarding GBM therapy, besides the study of survival mechanisms of GBM cells. 7 …”
Section: Introductionmentioning
confidence: 99%
“…7 GBM cells are radio- and chemo-resistant; therefore, ways to increase cell death are one of the major targets in GBM research. 8, 9, 10 Moreover, the parenchymal infiltration of GBM cells makes total surgical resection an impossible task, 11 rendering the study of tumor invasion mechanisms an issue regarding GBM therapy, besides the study of survival mechanisms of GBM cells. 7 …”
Section: Introductionmentioning
confidence: 99%
“…The human tumor cell lines, GBM02 and GBM11 cells, were established and characterized in our laboratory and maintained directly in DMEM/F12 supplemented with bovine serum after being collected from a GBM patient biopsy sample, as previously described [28], [29]. The human cell line OB1 was established and characterized by the laboratory of Dr. Hervé Chneiweiss and maintained in NS34 serum-free medium as described by Thirant et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…The SOX2, OCT-4A, NANOG, Cx43, Cx46, and Slug proteins were analyzed by Western blotting as originally described by Towbin and adapted by Balça-Silva and Kahn in both the GBM and GBM-SF cell lines [28], [32], [33]. Briefly, cells were centrifuged at 500× g for 10 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that low concentrations of EqTs are lethal, several studies have been reported on their effects on cancer cells [65,66,67]. Furthermore, they have been tested as the toxic moiety of immunotoxins targeting at Giardia duodenalis [68].…”
Section: Equinatoxinsmentioning
confidence: 99%